Development of Robust Tablet Formulations with Enhanced Drug Dissolution Profiles from Centrifugally-Spun Micro-Fibrous Solid Dispersions of Itraconazole, a BCS Class II Drug - Stefania Marano; Manish Ghimire; Shahrzad Missaghi; Ali Rajabi-Siahboomi; Duncan Q. M. Craig; Susan A. Barker (MDPI AG, 2023)
Fibre-based oral drug delivery systems are an attractive approach to addressing low drug solubility, although clear strategies for incorporating such systems into viable dosage forms have not yet been demonstrated. The present study extends our previous work on drug-loaded sucrose microfibres produced by centrifugal melt spinning to examine systems with high drug loading and investigates their incorporation into realistic tablet formulations. Itraconazole, a model BCS Class II hydrophobic drug, was incorporated into sucrose microfibres at 10, 20, 30, and 50% w/w. Microfibres were exposed to high relative humidity conditions (25 °C/75% RH) for 30 days to deliberately induce sucrose recrystallisation and collapse of the fibrous structure into powdery particles. The collapsed particles were successfully processed into pharmaceutically acceptable tablets using a dry mixing and direct compression approach. The dissolution advantage of the fresh microfibres was maintained and even enhanced after humidity treatment for drug loadings up to 30% w/w and, importantly, retained after compression into tablets. Variations in excipient content and compression force allowed manipulation of the disintegration rate and drug content of the tablets. This then permitted control of the rate of supersaturation generation, allowing the optimisation of the formulation in terms of its dissolution profile. In conclusion, the microfibre-tablet approach has been shown to be a viable method for formulating poorly soluble BCS Class II drugs with improved dissolution performance.